Environmental remediation through briquettes making from waste papers and latex - Nsanzamahoro Christophe; Ntizantererana Hyacinthe; Nyiransengimana Alexia Magnifique; Ciragani Pascal; Havumiragira Etienne; Uwayezu Janvier (BIORE Scientia Publisher, 2024)
This project is dedicated to mitigating the challenges associated with paper and glove waste disposal by introducing an environmentally conscious solution—carbonized briquettes designed for use as sustainable fuel. The methodology involves the meticulous combination of waste paper and gloves, followed by compression into briquettes and carbonization through pyrolysis. A thorough analysis was conducted to assess the quality of the resulting briquettes, focusing on combustion and physical properties. Noteworthy findings include approximately 11% volatile matters, 30 ppm of carbon monoxide, 0.56% moisture content, and over 76% fixed carbon. Physical properties exhibited 0.03% bulk density, 0.9% shattered index, and 0.81% tumbling test. Importantly, the experimental data attests to the project's minimal environmental impact, contributing positively to the overall well-being of the planet. The study's significance extends to environmental sustainability and remediation. It also sets the stage for future research endeavors, highlighting the need to optimize the briquette-making process, consider the glove-to-paper ratio, and develop effective glove cleaning methods to enhance safety for both users and makers. These refinements aim to fortify the project's potential for positive environmental and health outcomes. In summary, this project champions the conversion of paper and glove waste into eco-friendly fuel sources, offering a sustainable and promising solution to waste management challenges. The findings underscore its potential for widespread adoption, aligning with the principles of environmental sustainability and fostering a healthier planet for future generations.